Methods and Devices for Drying Agricultural Products - Shahodat, Sarimsaqova (American Journal of Biodiversity, 2025)
This article discusses the drying of fruits and vegetables under natural conditions in order to effectively use agricultural products. To create a device for drying fruits, vegetables and dairy products in natural conditions, he succeeded in drying melons and apples and made a simple device for this. The experiments were carried out over six days. Changes in their mass were recorded daily in three places, and tables and relationships were presented graphically. Also, the theoretical foundations are presented analytically in the form of equations and are completed with a brief summary and a list of references.